INTERNALIZED STIGMA, PERCEIVED SOCIAL SUPPORT, AND LIFE QUALITY IN PATIENTS ADMITTED TO A FORENSIC PSYCHIATRY UNIT - Kilicaslan, Asli Kazgan; Yildiz, Sevler; Emir, Burcu Sirlier; Kurt, Osman (Istanbul Univ, Fac Medicine, Publ Off, 2022)
Objective: This study aimed to examine internalized stigma, perceived social support, and the quality of life and its associations among patients admitted to a forensic psychiatry unit. Material and Method: A total of 97 patients treated at a High Security Forensic Psychiatry Unit were included. A Sociodemographic Data Form, the Multi-Dimensional Scale of Perceived Social Support (MSPSS), the Internalized Stigma of Mental Illness (ISMI), and the World Health Organization Quality of Life Short Form (WHOQOL) were administered to all patients. Results: The mean ISMI, MSPSS, and WHOQL scores were 74.3 +/- 8.4, 38.3 +/- 8.4, and 75.9 +/- 10.5, respectively. A negative correlation between the total MSPSS and total ISMI scores as well as between total the ISMI and total WHOQOL scores was found; on the other hand, a positive and significant association was determined between the total MSPSS and total WHOQOL scores (p<0.001, r=-0.367; p<0.001, r=-0.550; p<0.001, and r=0.496, respectively). The MSPSS total and sub-scale scores, age, alienation, stereotype endorsement, and perceived discrimination predicted the total WHOQOL score (R-2=0.613; Model F=12.242; p<0.001). Conclusion: Forensic psychiatry patients experience internalized stigma and reduced social support. Increasing levels of internalized stigma were associated with progressively lower levels of perceived social support and life quality. Predictors of the quality of life include the perceived social support, stereotype endorsement, discrimination, and alienation. This study sheds some light on factors affecting the quality of life in this relatively under examined group of forensic psychiatry patients.
ADLİ PSİKİYATRİ SERVİSİNDE TEDAVİ GÖREN HASTALARDA İÇSELLEŞTİRİLMİŞ DAMGALANMA, ALGILANAN SOSYAL DESTEK VE YAŞAM KALİTESİ
Keywords: Internalized stigmatization; perceived social support; quality of life; forensic psychiatry